Plasma Membrane Integrates Biophysical and Biochemical Regulation to Trigger Immune Receptor Functions - Zhang, Tongtong; Hu, Wei; Chen, Wei (Frontiers in Immunology, 2021)
Plasma membrane provides a biophysical and biochemical platform for immune cells to trigger signaling cascades and immune responses against attacks from foreign pathogens or tumor cells. Mounting evidence suggests that the biophysical-chemical properties of this platform, including complex compositions of lipids and cholesterols, membrane tension and electrical potential, could cooperatively regulate the immune receptor functions. However, the molecular mechanism is still unclear because of the tremendous compositional complexity and spatio-temporal dynamics of plasma membrane. Here, we review recent significant progresses of dynamical regulation of plasma membrane on immune receptors, including T cell receptor, B cell receptor, Fc receptor and other important immune receptors, to proceed mechano-chemical sensing and transmembrane signal transduction. We also discuss how biophysical-chemical cues couple together to dynamically tune the receptor’s structural conformation or orientation, distribution and organization, thereby possibly impacting their in-situ ligand binding and related signaling transduction. Moreover, we propose that electrical potential could potentially induce the biophysical-chemical coupling change, such as lipid distribution and membrane tension, to inevitably regulate immune receptor activation.